Match-related fatigue reduces physical and technical performance during elite rugby league match-play: a case study - Kempton, T.; Sirotic, A. C.; Cameron, M.; Coutts, A. J. (Journal of Sports Sciences, 2013)
This study examined the influence of match-related fatigue on physical and technical skill performance in ball playing positions at two different levels of rugby league competition. Time-motion analyses were performed using global positioning systems from 6 elite National Rugby League (NRL) and 11 junior elite National Youth Competition (NYC) players from 45 matches. A standardised 5-point technical coding criteria was used to qualitatively assess skill involvements during match-play. The distance travelled in the 0-5 and 40-45 min period were significantly higher compared to the 30-35, 35-40, 70-75 and 75-80 min periods (P < 0.001). Skill rating and involvements were higher in the 0-5 and 40-45 min compared to 70-75 and 75-80 min periods (P < 0.001 and P < 0.001, respectively).There was no significant difference in the number of physical collisions between the 5-min periods (P = 0.051). Following the peak 5-min bout of exercise intensity there were reductions in distance (P < 0.001), quality of skill involvements (P < 0.001), number of involvements (P < 0.001) and collisions (P < 0.001). Elite NRL and NYC "ball players" exhibit reductions in physical performance towards the end of matches and following brief periods of intense exercise. There also appears to be a reduction in technical performance for NRL and NYC ball players, which may be attributable to match-related fatigue.